Analyzing the Impact of COVID-19 Pandemic on Different Educational Aspects of Surgical Specialties’ Residency Program: A Preliminary Report - Abedi, Amir Reza; Shahmohammadi, Mohammadreza; Tadayon, Niki; Nazari, Leila; Hajimohammadebrahim-Ketabforoush, Melika; Sadighi, Mehrdad; Chehrassan, Mohammadreza; Jalili khoshnoud, Reza; Ghanbari, Mohammad Ali; Allameh, Farzad (Archives of Men's Health, 2021)
Introduction: The lifestyle and learning of trainees from different surgical specialties have been severely affected by the COVID-19 pandemic. Despite the growing body of research, the extent to which their surgical or educational performance is affected is not yet well-understood. We investigated the Iranian multi-specialty surgical residents nationwide to clarify the extent this new pandemic’s has affected their surgical and educational activities. Material and Methods: Our specialized board designed a questionnaire which was sent to residents from the 18th of May to 12th of Jun 2020. The questionnaire comprised demographic data, questions on the clinical, surgical, and educational activities during and before the pandemic. Results: Out of 700 eligible residents, 543 (77%) submitted their answers to all questions. 417 (76.8%) of the respondents declared they had spent their residency program at a hospital that was the main referral center for patients with COVID-19 infection. The weekly number of the outpatient and emergent visits decreased by one third (P<0.001) and one-half (P<0.001), respectively, following the pandemic. Also, the amount of surgeries has dramatically decreased (P<0.001). The median weekly hours devoted to face-to-face activities decreased, while the study time increased and the share of virtual education has a five-fold increase (P<0.001). Conclusion: This pandemic had a significant impact on many aspects of training in surgical specialties’ residency program in Iran. Increasing the time available to study is an opportunity, and online education, despite its challenges, has been effective.